Specifically neuropathic Gaucher's mutations accelerate cognitive decline in Parkinson's. Issue 5 (November 2016) - Liu, Ganqiang; Boot, Brendon; Locascio, Joseph J.; Jansen, Iris E.; Winder‐Rhodes, Sophie; Eberly, Shirley; Elbaz, Alexis; Brice, Alexis; Ravina, Bernard; van Hilten, Jacobus J.; Cormier‐Dequaire, Florence; Corvol, Jean‐Christophe; et al.
Abstract : Objective: We hypothesized that specific mutations in the β‐glucocerebrosidase gene ( GBA ) causing neuropathic Gaucher's disease (GD) in homozygotes lead to aggressive cognitive decline in heterozygous Parkinson's disease (PD) patients, whereas non‐neuropathic GD mutations confer intermediate progression rates. Methods: A total of 2, 304 patients with PD and 20, 868 longitudinal visits for up to 12.8 years (median, 4.1) from seven cohorts were analyzed. Differential effects of four types of genetic variation in GBA on longitudinal cognitive decline were evaluated using mixed random and fixed effects and Cox proportional hazards models. Results: Overall, 10.3% of patients with PD and GBA sequencing carried a mutation. Carriers of neuropathic GD mutations (1.4% of patients) had hazard ratios (HRs) for global cognitive impairment of 3.17 (95% confidence interval [CI], 1.60–6.25) and a hastened decline in Mini–Mental State Exam scores compared to noncarriers ( p = 0.0009). Carriers of complex GBA alleles (0.7%) had an HR of 3.22 (95% CI, 1.18–8.73; p = 0.022). By contrast, the common, non‐neuropathic N370S mutation (1.5% of patients; HR, 1.96; 95% CI, 0.92–4.18) or nonpathogenic risk variants (6.6% of patients; HR, 1.36; 95% CI, 0.89–2.05) did not reach significance. Interpretation: Mutations in the GBA gene pathogenic for neuropathic GD and complex alleles shift longitudinal cognitive decline in PD into "high gear." These findings suggest a relationship between specific types of GBA mutations and aggressive cognitive decline and have direct implications for improving the design of clinical trials. Ann Neurol 2016;80:674–685